Magnetic Nanoparticles with Core Shell: Macroscopic Model and Coercive Field - O. Hudak; M. Hudak (Advances in Materials Science and Engineering)
There exists nonhomogeneous structure in mechanosynthesized nanoparticles consisting of an ordered core surrounded by the shell. The shell may be structurally and magnetically disordered, or it may be ordered. These nanoparticles are found to be roughly spherical. We formulate the macroscopic model for the description of magnetic properties of nanoparticles with core-shell structure. The case of spheroids oriented in the same direction of polar axes is considered. There exits two coercive fields: Hcγ and Hcψ. They are depending on quantities o and x, where x=V2/(V1−2V2), and o=IF/IS , here V1 is the volume of the nanoparticle, and V2 is the volume of the core. IF is the magnetization of the core, and IS is the magnetization of the shell. There exists a transition from one type of the coercive field to another, changing x and o. We have found qualitative explanation of observed enhancement of coercive field and of its d-dependence in NiFe2O4 nanoparticles.